The effect of starch concentration on the gelatinization and liquefaction of corn starch. (June 2015) - Li, Zhaofeng; Liu, Wenjing; Gu, Zhengbiao; Li, Caiming; Hong, Yan; Cheng, Li
Abstract: Starch liquefaction is a key step in the industrial production of syrups, including those used in microbial fermentation processes. As part of an effort to improve the efficiency of this process, the effects of starch concentration on the gelatinization and liquefaction of corn starch were investigated. The results demonstrated that high starch concentrations in the slurry make it difficult to gelatinize the starch. Elevated starch concentrations inhibited swelling and disruption of starch granules and resulted in the retention of starch crystallinity after heat treatment. It became very difficult to destroy the granular and crystalline structure of the starch by heat treatment when the starch concentration exceeded 45%. Furthermore, elevated starch concentration had negative effects on the liquefaction of corn starch catalyzed by a thermostable α-amylase. The dextrose equivalent (DE) values of starch hydrolysates decreased as the starch concentration increased. Nevertheless, increasing the starch concentration from 30 to 45% caused only a slight reduction in the DE value of the hydrolysate, indicating that starch liquefaction at 45% starch could be comparable with that at 30%. Starch concentrations exceeding 45% severely retarded starch liquefaction. The relatively low degree of starch liquefaction seen at high starch concentrations, especially above 45%, was related to incomplete gelatinization of the starch, and low mobility of the water molecules and polymeric chains in the reaction system. These results provide additional insight into the feasibility of high-temperature liquefaction at high corn starch concentrations. Graphical abstract: Highlights: High starch concentrations made the gelatinization of starch difficult. Increasing starch concentration reduced the dextrose equivalent of the hydrolysate. The liquefaction of 45% starch slurry was comparable to that of 30% starch slurry. Increasing starch concentration above 45% severely retarded liquefaction. A low degree of liquefaction was related to incomplete gelatinization.